Comparison of Productivity and Efficiency Between Sharia and Conventional Banks Owned Government Period 2011-2018 - Farid Ahmad Hamidi; Aam Slamet Rusydiana (Ekonomi Islam Indonesia, 2019)
The purpose of this study is to analyze the comparison of the level of efficiency between time and the productivity of state commercial banks in Indonesia. State commercial banks in this case are grouped into 4 major groups including BUS, BUK, BPD, UUS. Measurement of the value of efficiency in this study uses the method of Data Envelopment Analysis (DEA). The use of the DEA method can measure the efficiency of banking by using many inputs and outputs. The continued application of the use of DEA is to use DEA Window Analysis, the result is the BUS has the best efficiency stability value with an average of 0.03 LDY then BUK with an average of 0.04, BPD with an average of 0.05 and UUS with an average an average of 0.09. Also this study wants to see the extent of the productivity of the country's commercial banks, the results using the Malmquist Index obtained BUS with the highest level of productivity with an average value of 1.008 then BPD with a value of 1.004, continued BUK 0.986 and UUS 0.964. Malmquist Index can also be used to identify where the source of the productivity value of an entity is obtained whether it comes from efficiency change or technological change so that by knowing these productivity factors it is expected that each bank can make corrections to the management of each company to increase their productivity